2012
DOI: 10.1270/jsbbs.61.653
|View full text |Cite
|
Sign up to set email alerts
|

Effects on flowering and seed yield of dominant alleles at maturity loci E2 and E3 in a Japanese cultivar, Enrei

Abstract: ‘Enrei’ is the second leading variety of soybean (Glycine max (L.) Merr.) in Japan. Its cultivation area is mainly restricted to the Hokuriku region. In order to expand the adaptability of ‘Enrei’, we developed two near-isogenic lines (NILs) of ‘Enrei’ for the dominant alleles controlling late flowering at the maturity loci, E2 and E3, by backcrossing with marker-assisted selection. The resultant NILs and the original variety were evaluated for flowering, maturity, seed productivity and other agronomic traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…The primers used were 5΄-TTTTCACTGACACACCAAGGTC-3΄ and 5΄-ACCTGCCAAAAGTGTACCAATC-3΄ for combi33; 5΄-AT T C G A C G T C T T C T C T C G TAT T-3΄ a n d 5΄ -TTGTACAGAGACCAGGGGAAAG-3΄ for combi12; 5΄-C G G T A T G A G C T G G T C A T G A A A -3 ΄ a n d 5΄-GCACGTGATCACACAGACAA-3΄ for LGIESSR1; 5΄-ACAAATTCTCAACATTGTAGCATCA-3΄ and 5΄-TGAAATTCATGTCCAGAACACA-3΄ for Scaffold_1_31. The four markers, E2at_U46k, E2at, E2at_D82k and GMES4019, were used for estimating E2 according to the previous study (Yamada et al, 2012). The four markers, E3at_U113k, FT3SSR4, FT3SSR1dom and FT3SSR3, were used for estimating E3 according to the previous study (Yamada et al, 2012).…”
Section: Field Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers used were 5΄-TTTTCACTGACACACCAAGGTC-3΄ and 5΄-ACCTGCCAAAAGTGTACCAATC-3΄ for combi33; 5΄-AT T C G A C G T C T T C T C T C G TAT T-3΄ a n d 5΄ -TTGTACAGAGACCAGGGGAAAG-3΄ for combi12; 5΄-C G G T A T G A G C T G G T C A T G A A A -3 ΄ a n d 5΄-GCACGTGATCACACAGACAA-3΄ for LGIESSR1; 5΄-ACAAATTCTCAACATTGTAGCATCA-3΄ and 5΄-TGAAATTCATGTCCAGAACACA-3΄ for Scaffold_1_31. The four markers, E2at_U46k, E2at, E2at_D82k and GMES4019, were used for estimating E2 according to the previous study (Yamada et al, 2012). The four markers, E3at_U113k, FT3SSR4, FT3SSR1dom and FT3SSR3, were used for estimating E3 according to the previous study (Yamada et al, 2012).…”
Section: Field Test Proceduresmentioning
confidence: 99%
“…The four markers, E2at_U46k, E2at, E2at_D82k and GMES4019, were used for estimating E2 according to the previous study (Yamada et al, 2012). The four markers, E3at_U113k, FT3SSR4, FT3SSR1dom and FT3SSR3, were used for estimating E3 according to the previous study (Yamada et al, 2012). Toyoharuka and Hayahikari were used as the references for e1e1 e2e2 E3E3 E4E4 and E1E1 e2e2 e3e3 e4e4, respectively.…”
Section: Field Test Proceduresmentioning
confidence: 99%
“…‘Enrei’ controls early flowering by the recessive alleles e2 and e3 (Yamada et al. ). Our results showing differences in photosensitivity for flowering between ‘Enrei’ and ‘Peking’ are consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, NILs of the Japanese cultivar 'Enrei' have now been developed through marker assisted selection (Yamada et al, 2012). 'Enrei' is so far the only Japanese soybean cultivar to have had its whole genome sequenced (Shimomura et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…E1 is reported to be a repressor of GmFT2a and GmFT5a, orthologues of FLOWERING LOCUS T of Arabidopsis (Xia et al, 2012); E2 is reported to be an orthologue of the GIGANTEA gene of Arabidopsis, related to a circadian clock (Watanabe et al, 2011); and E3 and E4 are reported to be phytochrome A (phyA) genes sensitive to the ratio of red light to far-red light (R:FR ratio), named as GmphyA3 and GmphyA2, respectively (Liu et al, 2008;Watanabe et al, 2009). Yamada et al (2012) developed NILs of maturity genes E2 and E3 of 'Enrei', and compared seed yield and basic agronomic traits at several locations in Japan. Although Yamada et al observed a significant difference in growth duration and seed yield between 'Enrei' and the NILs, the key traits differentiating seed yield were not revealed.…”
Section: Introductionmentioning
confidence: 99%